Numerical study of film cooling over a flat plate with anisotropic thermal conductivity. (25th January 2017) - Tu, Zecan; Mao, Junkui; Han, Xingsi
Highlights: Film cooling over a flat plate with anisotropic thermal conductivity was investigated. The variations of the main direction in thermal conductivities were accounted for. Both the mean value of cooling effectiveness and its distribution uniformity were examined. Cooling performances in different special regions on the target surface were discussed. Abstract: Numerical study was performed to investigate the film cooling performance for a flat plate with anisotropic thermal conductivity where the plate had a single row of round holes. The cooling effectiveness and temperature distribution were analyzed and compared between the results of isotropic and anisotropic plates. The effects of two angles on the cooling effectiveness were studied, i.e. the axial angle α (0°, 30°, 35°, 60° and 90°) and the spanwise angle β (0°, 30°, 60° and 90°), with regards to the inclined angle between the main thermal conductivity in the plate and the mainstream flow direction. The results obtained showed that the anisotropy of the thermal conductivity and the inclined angles affected the cooling effectiveness in a complex way. The highest average cooling effectiveness could be achieved with a specific α or β, depending on the downstream region of the film cooling hole being considered. With the blowing ratio Br = 0.5, the highest cooling effectiveness averaged over the 0–5D and 0–20D downstream regions (with D the diameter of the film cooling hole) could be obtained with an angle of around 35° and 90° for α, respectively. It was found that the uniformity of the cooling effect was improved with a larger β. Moreover, the effects of α and β on the average cooling effectiveness were found to be similar with different Br. However, the uniformity was affected by α and β non-monotonically in different cases of Br. This work demonstrates that proper inclined angle can lead to better film cooling performance.